ANALISIS FAKTOR PSIKOLOGIS TERHADAP PENCAPAIAN AKADEMIK SISWA SMK: STUDI PADA PEMBELAJARAN KELISTRIKAN OTOMOTIF - Mikhael Owen Sitorus; Toto Sugiarto; Hasan Maksum; Rifdarmon Rifdarmon (Ensiklopedia of Journal, 2026)
This research seeks to examine the impact of learning interest and motivation on Final Semester Examination (UAS) outcomes in the Light Vehicle Electrical Maintenance course at SMK Negeri 4 Pariaman. The study used a quantitative methodology using a correlational design. The population included all 26 students in class XI Automotive Engineering, using a saturation sample approach. Research tools included Likert scale questionnaires to assess learning interest and motivation, together with UAS score recording. The data analysis used multiple linear regression facilitated by SPSS. The findings indicated that: (1) learning interest did not significantly affect UAS results (sig. 0.424 0.05); (2) learning motivation did not significantly affect UAS results (sig. 0.340 0.05); and (3) the combined effect of learning interest and motivation did not significantly affect UAS results (F = 0.495; sig. 0.616 0.05), with a R² value of merely 4.1%. The results suggest that elements such as the quality of practical facilities, instructor ability, and instructional strategies have a more significant effect in student learning outcomes in productive disciplines.Keywords: Learning Interest, Learning Motivation, Learning Outcomes, Light Vehicle Electrical, Vocational High School